Esther Greenwoodâs Psychological Conflicts Reflected in Sylvia Plathâs The Bell Jar (1963): A Psychoanalytic Criticism - Fadlila, Zenithda Arief (JoLLIET, 2014)
The research is proposed to analyze Esther Greenwoodâs psychological conflicts in The Bell Jar novel by using Psychoanalytic Criticism. The major problem in this article is to explain how the psychological conflict is reflected in Sylvia Plathâs The Bell Jar.The object of study is The Bell Jar novel written by Sylvia Plath. Qualitative study is a method which is used to analyze the psychological conflicts reflected in the novel. The result of this study shows that in this novel Sylvia Plath illustrated a psychological phenomenon in which an individual encounters an inner conflict that requires resolution.